Penguatan Kemandirian Anak Berkebuhan Khusus (ABK) Melalui Pemberdayaan di bidang Keterampilan Kuliner dan Kerajinan Tangan Budaya Jepang di LKP Ceria Surabaya - Novi Andari; Khasanah, Umul (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
One of the goals of education is to develop students' potential and have the skills needed by children with special needs to be independent and economically empowered. One of the skills that can be given to children with special needs is culinary skills and handicrafts. Japan and its culture are known throughout the world, including Indonesia. There have been many small and medium entrepreneurs who have successfully run businesses in the Japanese culinary and handicraft sector. LKP Ceria, which is located in Ngagel Tirto Surabaya, has one mission that its students are expected to be able to create products and be competitive in society. The aim of LKP Ceria is to encourage its students to become financially independent. In line with this, the PkM program aims to empower LKP Ceria Surabaya students by developing culinary skills and handicrafts from Japanese culture to equip them for business and as a source of financial income that supports independent living and is ready to compete in society. The culinary delights that will be taught are takoyaki and okonomiyaki. Meanwhile, the handicrafts that will be taught are Japanese dolls and various folding arts that are useful in daily life, for example wrapping boxes. Apart from that, students will be taught how to use e-commerce as an online selling medium which makes it easier for them to market their products. LKP Ceria Surabaya has students consisting of 3 levels of education, namely from elementary school to high school, so that the skills material that will be provided is adjusted to the capacity of each of their educational levels.